Identifikasi Sleep Hygiene Lansia di Panti Sosial Tresna Werda Budi Luhur Jambi - Muhammad Hidayat (Universitas Baiturrahim, 2021)
The degenerative process in the elderly will cause a decrease in function, one of which is physiological function. The decrease in physiological function that is most often experienced by the elderly is a decrease in the need for rest and sleep. Sleep needs that are met both in quality and quantity can improve the quality of life. One of the best ways to achieve good sleep in the elderly is sleep hygiene. Sleep can be influenced by an exercise or good habits called sleep hygiene. An exercise or good sleep habits can prevent the development of sleep disorders. This study aims to determine the description of the sleep hygiene of the elderly at the Tresna Werda Social Panti (Pstw) Budi Luhur Jambi. This study is a non-experimental type of research with a descriptive survey design, using quantitative methods, and a cross sectional approach. The results provide information that the majority or 36 of the 55 elderly people are female. Sleep hygiene scores for the elderly at the Tresna Werda Social Institution (Pstw) Budi Luhur Jambi 38 people were categorized as good, 14 people were categorized as poor and 3 people were categorized as bad. It can be concluded that the sleep hygiene score for the elderly at the Tresna Werda Social Home (Pstw) Budi Luhur Jambi is mostly categorized as good